Intoxicação em bovinos por Senna occidentalis - Carmo, Priscila Maria Silva do (2011)
Sixteen outbreaks of Senna occidentalis (coffee senna) occurring in cattle from the state of Rio Grande do Sul, Brazil, were reviewed. The great majority (75%) of the outbreaks occurred in adult cattle at pasture during the autumn and winter months with 50% occurring in May, evidencing a striking seasonality. Mortality rates varied from 4.2% to 55.2% and cattle died 2 days up to 2 weeks after showing clinical signs that included dry feces (occasionally diarrhea), muscle weakness, reluctance to move, tachypnea, instability of the hind limbs with dragging of the toes, tremors in muscles of the thighs, neck, and head, ear dropping, sternal recumbency, lateral recumbency and death. Myoglobinuria characterized by a dark red or black discolored urine was a consistent finding in cattle affected at pasture but not in those poisoned by ration contaminated with coffee senna beans. Creatine phosphokinase serum activity was markedly elevated. Main gross changes observed in 23 necropsies involved skeletal muscles of the hind limbs. These changes consisted of varying degrees of paleness of muscle groups. Subepicardial and subendocardial hemorrhages were present in the hearts of all affected cattle. Histologically a segmental degenerative myopathy of striated muscles was present in every case and had a multifocal polyphasic or monophasic character. Myocardial (3/23), hepatic (3/13), renal (3/10), and splenic (1/6) microscopic lesions were observed occasionally. Myocardial lesions were mild and consisted of vacuolation of cardiomyocytes or focal fibrosis. Hepatic changes consisted of diffuse hepatocellular vacuolation, cytosegrosomes within hepatocytes, and individual hepatocellular necrosis. Kidneys have vacuolar degeneration of tubular epithelium associated with acidophilic casts (proteinosis) within tubular lumina. In the spleen there was marked necrosis of lymphocytes of the white pulp. No histological changes were found in the brains of 13 affected cattle. The data of this study suggest that coffee senna poisoning is an important cause of death in cattle in southern Brazil. The epidemiological, clinical and pathological features described in the study shoud be useful for diagnosing the condition in the field.